Membrane Interactome of a Recombinant Fragment of Human Surfactant Protein D Reveals GRP78 as a Novel Binding Partner in PC3, a Metastatic Prostate Cancer Cell Line - Thakur, Gargi; Sathe, Gajanan; Kundu, Indra; Biswas, Barnali; Gautam, Poonam; Alkahtani, Saad; Idicula-Thomas, Susan; Sirdeshmukh, Ravi; Kishore, Uday; Madan, Taruna (Frontiers in Immunology, 2021)
Surfactant Protein-D (SP-D), a member of collectin family of pattern recognition receptors, has been shown to induce apoptosis in cancer cells. SP-D is composed of an N-terminal collagen-like domain and a calcium-dependent Carbohydrate Recognition Domain (CRD). Recently, we reported that a recombinant fragment of human SP-D (rfhSP-D) composed of homotrimeric CRD region induced intrinsic apoptotic pathway in the prostate cancer cells. Here, we analyzed the membrane interactome of rfhSP-D in androgen-independent prostate cancer cells, PC3, by high resolution mass spectrometry and identified 347 proteins. Computational analysis of PPI network of this interactome in the context of prostate cancer metastasis and apoptosis revealed Glucose Regulated Protein of 78 kDa (GRP78) as an important binding partner. Docking studies suggested that rfhSP-D (CRD) binds to the substrate-binding domain of glycosylated GRP78. This is further supported by the observations that human recombinant GRP78 interfered with the binding of rfhSP-D to the anti-SP-D polyclonal antibodies, and GRP78 significantly inhibited the binding of recombinant full-length human SP-D with a monoclonal antibody against the CRD of SP-D in a dose-dependent manner. We suggest that the interaction with rfhSP-D is likely to interfere with the pro-survival signaling of GRP78.